Literature Riview: Analisis Capaian KB Aktif dan Kontrasepsi pada Masa Pandemik Covid-19 - Anggit Yanuaristi; Dean Wahjudi Satyaputra; Lelly Yuniarti (Bandung Conference Series: Medical Science, 2023)
Abstract: The government established a PSBB policy in 2020 to break the chain of distribution of COVID-19 by limiting people's mobility towards social contact, this has an impact on limited access to health services. This study aims to examine the achievements of active family planning and contraception programs during a pandemik by using the literature review method to identify published literature using relevant keywords. Based on the literature review produced, active KB acceptors decreased during a pandemik, contraceptive methods that experienced a decrease included MOP, pills, injections and MOW. Contraceptives that have increased in IUDs, Implants and Condoms. In conclusion, the results of active family planning decreased due to COVID-19, the distribution of contraceptives was made easier for the community and family planning services were further improved to prevent the "baby boom" at the end of the COVID-19 pandemic. Abstrak: Pemerintah menetapkan kebijakan PSBB pada tahun 2020 utuk memutus mata rantai penyebaran COVID-19 dengan cara membatasi mobilitas masyarakat terhadap kontak sosial, hal tersebut berdampak pada terbatasnya masyarakat mendapatkan layanan kesehatan. Penelitian ini bertujuan untuk meneliti capaian program KB aktif dan kontrasepsi pada masa pandemik dengan menggunakan metode literature review untuk mengidentifikasi literature yang telah dipublish dengan menggunakan kata kunci yang relevan. Berdasarkan dari literature riview dihasilkan, Akseptor KB aktif menurun pada saat pandemik, alat kontrasepsi yang mengalami penurunan diantaranya MOP, Pil, Suntik dan MOW. Alat kontrasepsi yang mengalami peningkatan pada IUD, Implant dan Kondom. Simpulan, capaian KB aktif menurun dipengaruhi oleh COVID-19, distribusi alat kontrasepsi dipermudah untuk masyarakat dan pelayanan KB lebih ditingkatkan untuk mencegah “baby boom” pada akhir masa pandemik COVID-19.